1998
DOI: 10.1210/jcem.83.3.4788
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Alpha (ER-α) and Beta (ER-β) mRNAs in Normal Ovary, Ovarian Serous Cystadenocarcinoma and Ovarian Cancer Cell Lines: Down-Regulation of ER-β in Neoplastic Tissues

Abstract: The prognosis in ovarian carcinoma, the most lethal of the gynecologic neoplasms, is poor and has changed little in the last three decades. Only a small number respond to antiestrogen therapy, although the classic estrogen receptor, ER-alpha, has been identified in ovarian surface epithelium, from which approximately 90% of ovarian cancers originate. We have previously shown that ER-beta mRNA is most abundant in human fetal ovaries, suggesting that it might play an important role in ovarian development. Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 0 publications
4
26
0
1
Order By: Relevance
“…In addition, equal or increased ERα mRNA expression in conjunction with a decreased ERβ mRNA expression indicates differential roles for ERα-and ERβ-driven pathways during breast and ovarian tumorigenesis. 7,8) In our results, Wt ERα mRNA showed a stepwise decrease from normal or G1 through to G3 tumors, in line with changes in the protein expression determined by both immunohistochemistry and western blot assay, in contrast to Wt ERβ mRNA or protein expression, which did not alter. It is therefore suggested that changes in the ratio of two ER subtypes may cause alteration in estrogen signaling pathways during endometrial tumorigenesis.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In addition, equal or increased ERα mRNA expression in conjunction with a decreased ERβ mRNA expression indicates differential roles for ERα-and ERβ-driven pathways during breast and ovarian tumorigenesis. 7,8) In our results, Wt ERα mRNA showed a stepwise decrease from normal or G1 through to G3 tumors, in line with changes in the protein expression determined by both immunohistochemistry and western blot assay, in contrast to Wt ERβ mRNA or protein expression, which did not alter. It is therefore suggested that changes in the ratio of two ER subtypes may cause alteration in estrogen signaling pathways during endometrial tumorigenesis.…”
Section: Discussionsupporting
confidence: 83%
“…6) Although changes in the expression of two ER subtypes have been documented during breast and ovarian tumorigenesis, 7,8) little is known about the endometrial carcinoma case.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…In 1996, a new ER (ERb) was discovered and was found to be genetically distinct from the classical ER (ERa) (Kuiper et al 1996). Since then, ERb has been found in most estrogen-target tissues such as the prostate (Weihua et al 2001) and the ovary (Brandenberger et al 1998). Reduced levels of ERb mRNA expression were found in malignant tissues compared with normal tissues in various estrogendependent tumors such as breast, prostate, and ovarian cancers (Iwao et al 2000, Horvath et al 2001, Skliris et al 2003, Chan et al 2008, indicating that the loss of ERb expression may be involved in carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Hillier et al (1998) have recently shown that both ERa and ERb are expressed in human normal ovarian surface epithelial cells in culture. Others and we have shown an increase in the ERa:ERb mRNA ratio in ovarian cancers compared to normal ovaries, suggesting the possible involvement of ERa-related genes in ovarian tumor progression Brandenberger et al, 1998;Rutherford et al, 2000).…”
Section: Introductionmentioning
confidence: 55%